Islamic social finance integration: the iTEKAD case in Malaysia / Dr. Mohamad Hanif Abu Hassan, Dr. Wahidah Shari and Dr. Muhammad Zarunnaim Haji Wahab - Abu Hassan, Mohamad Hanif; Shari, Wahidah; Wahab, Muhammad Zarunnaim (Universiti Teknologi MARA, Kedah, 2023)
The rise in poverty, unemployment, and various social problems, coupled with limited public spending, has underscored the importance of enterprises that aim to generate positive social impact alongside financial economic benefits (Hassan & Yahya, 2020). These social impact enterprises play a crucial role in the growth and development of economies, yet accessing finance remains a significant challenge for them. Traditional financial instruments have become increasingly difficult to obtain, particularly after the recent financial crisis, leaving social enterprises at a disadvantage due to their perceived high risk, governance issues, and the lack of standardized performance measurement for social value (Abu Al-Haija et al., 2021; Hassan et al., 2020) To address these pressing issues, it is essential to emphasize the understanding of social entrepreneurship and social enterprise, particularly in the context of Islamic social finance.